Indigenous Tswana architecture: with specific reference to the Tshidi Rolong village at Mafikeng - McLean, Diane Lynn (Rhodes University, Faculty of Humanities, Department of Fine Art, 1986)
This essay is divided roughly into two main sections; in the first I have discussed the Tswana as a whole, their environment, their origins and their more recent history. In addition to this, I have tried to give a clear picture of their tribal political structure and economic activities, as well as their domestic activities, all of which are integrally linked to the kind of house form adopted by the Tswana. The last, and most important, part of the first section is a presentation of some of the earliest written descriptions of Tswana dwellings made by the first white travellers to enter Tswana territory. The second section takes the form of a presentation of findings observed during the course of personal field research undertaken in the Tshidi-Rolong village outside Mafikeng. This research was done by means of a number of questionnaires drawn up by myself and filled in on the spot with information supplied by house owners and sometimes the builders themselves. This survey was carried out largely at random, with several of the houses chosen arbitrarily because of an interesting feature which set them apart from other dwellings. This written information is backed up by a large bulk of visual information in the form of photographs taken personally, both of the dwellings in general, and of details of the houses. Although this essay may appear to be rather fragmented, my aim is to give a graphic account of changes in Tswana dwellings by comparing features of contemporary dwellings with those observed in the early nineteenth century. The fact that among the Tswana , the building style of one sub-tribe may vary slightly from that of another subtribe, has not affected my study to any large extent , since I was fortunate enough to have done my field research among a branch of one of the original groups, namely the Rolong, whose houses, along with those of the Tlhaping, were the first to be documented. Therefore, most of the differences which have occurred between the dwellings of the contemporary Tshidi-Rolong and those from the early nineteenth century are a direct result of the process of westernisation.
Keywords: Architecture -- South Africa -- North-West; Architecture, Domestic -- South Africa -- North-West